Analisis Manajemen Risiko Berbasis ISO 31000 pada Usaha Konveksi - Dewi Resti Agustiani; Yesica Maulina; Alifa Raudhatul Nisa; Ashilah Fauziyah; Alfiana (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study analyzes the operational aspects and business feasibility of sewing convection enterprises within the MSME sector in Indonesia. the research focuses on key business performance components such as production processes, cost structures, risk management, labor management,and marketing strategies. using a qualitative descriptive approach and a case study method, data were collected through observations, interviews, and documentation. the findings indicate that convection businesses have strong growth potential driven by increasing demand for custom clothing, school and office uniforms, and small batch production. the production process consists of pattern making, fabric cutting, sewing, finishing, and quality control—each stage playing a crucial role in ensuring product quality and timely delivery. the cost structure is mainly influenced by raw materials, labor wages, utilities, and machine maintenance. The main risks identified include delays in material supply, machine breakdowns, production errors, inconsistent product quality, and miscommunication in customer orders. Effective labor management, particularly through skill development, is essential in minimizing these risks. Marketing strategies that enhance competitiveness include the use of social media, competitive pricing, customization services, and maintaining consistent quality.